Elucidating the Molecular Basis of Avibactam‐Mediated Inhibition of Class A β‐Lactamases. Issue 43 (9th July 2020) - Das, Chandan Kumar; Nair, Nisanth N.
Abstract: Disseminating antibiotic resistance rendered by bacteria against the widely used β‐lactam antibiotics is a serious concern for public health care. The development of inhibitors for drug‐resistant β‐lactamase enzymes is vital to combat this rapidly escalating problem. Recently, the U.S. Food and Drug Administration approved a non‐β‐lactam inhibitor called avibactam for the treatment of complicated intra‐abdominal and urinary tract infections caused by drug‐resistant Gram‐negative bacteria. This work sheds light on the molecular origin of the inhibitory effect of avibactam against the drug‐resistant CTX‐M variant of class A β‐lactamases. In particular, we probed the structural evolution, dynamics features, and energetics along the acylation and deacylation reaction pathways through enhanced sampling molecular dynamics methods and free‐energy calculations. We scrutinized the roles of active site residues, the nature of the carbamoyl linkage formed in the inhibitor–enzyme covalent intermediate, and other structural features of the inhibitor molecule. By unraveling the reasons behind the inhibition of all the deacylation routes, we can explain various experimental structural and kinetics data, and propose a way to design new inhibitors based on the β‐lactam framework. Abstract : Solving the resistance ! This computational study reveals the molecular basis of the avibactam‐mediated inhibition of the drug‐resistant CTX‐M variant of class A β‐lactamases. By unraveling the reasons behind the inhibition of all the deacylation routes, we explain various experimental structural and kinetics data, and propose a way to design new inhibitors based on the β‐lactam framework.